FAKTOR - FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN - Octaviani, Erica Safira; Maria, Maria (E-Jurnal Akuntansi TSM, 2023)
The purposes of this study is to obtain empirical evidence on the factors that influence the variables of profitability, firm size, leverage, price earnings ratio, corporate social responsibility, and audit committee on firm value. This study is used samples from consumer non cyclicals and consumer cyclicals companies listed on the Indonesia Stock Exchange in the period 2020 to 2022. The sample selection method was carried out using purposive sampling method, as a result there were 54 companies with a total of 162 data used. This study used multiple regression analysis to analyze the data. The results of this study indicate that there is an influence between profitability and price earnings ratio on firm value. Meanwhile, firm size, leverage, corporate social responsibility and audit committee have no effect on firm value.